2000
DOI: 10.1177/1329878x0009600104
|View full text |Cite
|
Sign up to set email alerts
|

Back to the Future

Abstract: A quarter of a century ago, Telstra's predecessor — Telecom Australia — attempted something that would be unthinkable in today's environment: it set out to provide a roadmap to the industry future 25 years ahead. Telecom 2000 fairly accurately predicted the major developments in technology, but was less successful in anticipating the changes in industry economics and structure, and the contest between market forces and the then-prevailing public utility model of service delivery. This article reviews the Telec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2015
2015

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…MyBurb had indirect support through Australian legislation that suggests the ABC should continually innovate (ABC Act, 1983) where the ABC is a key cultural institution under Schedule 5 of the Copyright Regulations Act (1969). Market research suggested that the ABC is a key social innovation driver in the Australian media market (Cutler, 2008) as a response “to changes in the media environment arising from digitisation, convergence and changing societal needs and expectations” (Flew, Cunningham, Bruns, & Wilson, 2008, p. 1). At a national level, independent media enquiries were beginning to surface that questioned the role of Australian PSM in a digital, converged environment, highlighting the necessity for the ABC to be focussing on the digitization of archives for improved public access.…”
Section: Public Service Media and The Abc As A Digital Archive Institmentioning
confidence: 99%
“…MyBurb had indirect support through Australian legislation that suggests the ABC should continually innovate (ABC Act, 1983) where the ABC is a key cultural institution under Schedule 5 of the Copyright Regulations Act (1969). Market research suggested that the ABC is a key social innovation driver in the Australian media market (Cutler, 2008) as a response “to changes in the media environment arising from digitisation, convergence and changing societal needs and expectations” (Flew, Cunningham, Bruns, & Wilson, 2008, p. 1). At a national level, independent media enquiries were beginning to surface that questioned the role of Australian PSM in a digital, converged environment, highlighting the necessity for the ABC to be focussing on the digitization of archives for improved public access.…”
Section: Public Service Media and The Abc As A Digital Archive Institmentioning
confidence: 99%